Efektivitas E-Booklet Pendidikan Kesehatan terhadap Pengetahuan Ibu Hamil Tanda Bahaya Kehamilan di Puskesmas Sonomartani Labura - Nurhabib Nurhabib; Retno Wahyuni; Rumondang Sitorus (Lembaga Pengembangan Kinerja Dosen, 2024)
Early detection of high risk by health workers through quality antenatal care is one of the efforts to accelerate the reduction of MMR in Indonesia. The aim of this research was to determine